Relined metal denture base: An alternative procedure for atrophied mandibular ridge - Priyanka Bajaj; Ajay Kumar Nayak; R B Hallikerimath (Wolters Kluwer Medknow Publications, 2009)
Severe resorption of the mandibular alveolar ridge contributes to instability and discomfort of the conventional acrylic resin dentures. Alveolar ridge resorption may be corrected, in part, by various surgical techniques. But when surgery is not feasible, the need for a mandibular denture that is strong, stable and functional can be met by a metal-based denture. This article describes the clinical and laboratory procedures to incorporate a metal frame at a pre-determined, controlled position within the prosthesis. This procedure provides not only stability and strength but also ensures space for a resilient liner.